Fellowship Trainee Research Activities of a Faculty of Bangladesh College of Physicians and Surgeons: Analysis of 30 years Dissertation Work and Recommendation for Further Improvements - Uddin , Taslim; Kamal, Tahmeed; Azad, AK; Islam, Md Jahidul; Yousuf, Mohammad; Moyeenuzzaman, Md (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Physical Medicine and Rehabilitation (PMR) is a diverse specialty with principal focus on disability evaluation and functional restoration of an individual. The PMR Faculty at Bangladesh College of Physicians and Surgeons (BCPS) was established about 30 years ago. As a medical specialist of 21st century, at this point of time, it is important to know and evaluate the spectrum of research activities performed by the trainees of the faculty. Objectives of the study was to make an in-depth analysis of the dissertations completed by the PMR fellow trainees of BCPS since the inception of the Faculty. It was also aimed to discuss the strengths and insights of shortcoming of the research areas and topics with directives for further improvement of the future trainees and faculties ultimately to initiate a dialogue among the stake holders and other specialties. This was an observational mixed method study. Information was gathered from the BCPS webpage, Faculty office and published materials, which was further strengthened with a small group discussion, online literature search and a telephone interview of the PMR fellows to learn their experience that they gained during the dissertation works. A total of 167 (n=167) dissertation topics were available for statistical analysis submitted by the trainee fellows from 1992 to 2021, a period of 30yrs. More than half (50.9%) of the submitted titles were on effectiveness or comparative study of rehabilitation therapy modalities which include therapeutic -electrophysical -agents(TEA), exercises, occupational therapy or orthotics. Musculoskeletal (MSK) and rheumatological disorders constituted (17.4%), neurological disorder 7.1%), risk factor assessment or etiological pattern of MSK conditions (7.2%), disability and functional outcome assessment (5.4%), interventions for regional pain management (4.8%) and other category (7.2%). The initial decade trend was on MSK, which later shifted to TEA and on interventions respectively. Overall, TEA modalities were the predominating titles in all 3 decades. Considering the other category of titles, there were interesting topics which include COVID-19, variation in body mass composition, assessment of drug effects, diagnostics and effectiveness of educational booklet. Of the 09 dissertations approved during the most recent year (2021), 34% were with interventional pain management. In the process of doing a dissertation, a number of opportunities and challenges were identified by the fellows for fellow trainee researchers. There was a clear trend of dissertation titles on MSK pain management and interventions with less attention to rehabilitation procedure and appliances. Identified opportunities include cooperative attitude of the trainers and mentors in the department and there were wide research areas with vast sample population. Time allocation and funding were the biggest barriers for research works during training period. BCPS to support on research methodology, fund placements and to catalyze with other institutes to ensure a reasonable level comfort for research works. J Bangladesh Coll Phys Surg 2022; 40: 51-56